ANALISIS SEBARAN IDIOM DALAM NEW HSK DAN NEW STANDARD HSK - Nadya, Jenny; Sutandi, Septerianie (Universitas Pendidikan Ganesha, 2024)
Currently there are two versions of the Chinese Proficiency Test (HSK) exam held by Hanban to measure Chinese language proficiency for non-native speakers, namely New HSK and New Standard HSK. HSK not only includes vocabulary, but also includes idioms, but there is a significant accumulation of idioms at the highest level in both exams. In contrast to most other studies of Chinese idioms which focus more on learning methods, in this research author analyses the distribution of idioms contain in the New HSK and New Standard HSK exams with the aim to provide suggestions for updating the application of idioms in both exams. This research uses descriptive research methods with a qualitative approach. The results of this research can be concluded that the distribution of idioms in the New HSK and New Standard HSK exams does not have gradation of increasing numbers from lower levels to higher levels. Therefore, author suggests Hanban to spread idioms that are relatively easy and whose meaning can be understand directly to lower exam levels by appearing in listening and reading sections and increasing the intersection of idiom between New HSK and New Standard HSK. The implication of these updating suggestions are expected to make it easier for teachers and students to prepare for exams, teach idioms earlier in the context of everyday life, increase practice in applying idioms which are the intersection of New HSK and New Standard HSK, and introduce idioms using explaining the culture or history behind an idiom. Keywords : HSK, New HSK, New Standard HSK, idioms, learning. Abstrak Saat ini terdapat dua versi ujian Hanyu Shuiping Kaoshi (HSK) yang diadakan oleh Hanban untuk mengukur kemahiran berbahasa Mandarin penutur asing, yaitu New HSK dan New Standard HSK. Soal HSK tidak hanya meliputi kosakata sehari – hari, tetapi juga meliputi idiom, namun terjadi penumpukan jumlah idiom yang signifikan pada level atas dalam ujian New HSK dan New Standard HSK. Berbeda dengan kebanyakan penelitian idiom bahasa Mandarin lainnya yang lebih banyak menyoroti metode pembelajarannya, dalam penelitian ini dilakukan analisis sebaran idiom yang terdapat dalam ujian New HSK dan New Standard HSK dengan tujuan untuk memberikan saran pembaharuan penerapan idiom dalam kedua ujian tersebut. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kualitatif. Hasil dari penelitian ini dapat disimpulkan sebaran idiom pada ujian New HSK dan New Standard HSK tidak memiliki gradasi peningkatan jumlah dari level rendah menuju level yang lebih tinggi. Oleh karena itu Hanban perlu untuk menyebar idiom-idiom yang relatif mudah dan maknanya dapat dipahami secara langsung ke level ujian yang lebih rendah, memunculkan idiom-idiom yang mudah dipahami pada soal ujian level rendah bagian mendengar (listening) dan membaca (reading) dengan konteks sehari-hari, dan meningkatkan interseksi kemunculan idiom antara New HSK dan New Standard HSK. Implikasi dari pembaharuan yang disarankan dapat memudahkan pengajar dan pemelajar mempersiapkan diri mengikuti ujian, dapat lebih dini mengajarkan idiom dalam konteks kehidupan sehari – hari, memperbanyak latihan penerapan idiom yang merupakan interseksi New HSK dan New Standard HSK, dan memperkenalkan idiom dengan metode bercerita budaya atau sejarah di balik sebuah idiom.